Angiosome-directed endovascular intervention and infrapopliteal disease: Intraoperative evaluation of distal hemodynamic changes and foot blood volume of lower extremity - Wang, Chaonan; Chen, Junye; Lei, Jinsong; Shao, Jiang; Lai, Zhichao; Li, Kang; Cao, Wenteng; Liu, Xiaolong; Yuan, Jinghui; Liu, Bao (Frontiers in Surgery, 2022)
Objectives To evaluate foot blood volume and hemodynamics and explore whether quantitative techniques can guide revascularization. Materials and methods A prospective single-center cohort study included thirty-three patients with infrapopliteal artery occlusion who underwent percutaneous transluminal angioplasty (PTA) between November 2016 and May 2020. The time-to-peak (TTP) from color-coded quantitative digital subtraction angiography (CCQ-DSA) and parenchymal blood volume (PBV) were used to evaluate the blood volume and hemodynamic changes in different regions of the foot before and after the operation. Results After the intervention procedure, the overall blood volume significantly increased from 25.15 ± 21.1 ml/1,000 ml to 72.33 ± 29.3 ml/1,000 ml (p < 0.001, with an average increase of 47.18 ml/1,000 ml. The overall TTP decrease rate, postoperative blood flow time significantly faster than those preoperatively, from 22.93 ± 7.83 to 14.85 ± 5.9 s (p < 0.001, with an average decrease of 8.08 s). Direct revascularization (DR) resulted in significant blood volume improvement than compared with indirect revascularization (IR) [188% (28, 320) vs.51% (10, 110), p = 0.029]. Patients with DR had a significantly faster blood flow time than those with IR [80% (12, 180) vs. 26% (5, 80), p = 0.032]. The ankle-brachial index (ABI) of the affected extremity also showed an significant change from 0.49 ± 0.3 to 0.63 ± 0.24 (p < 0.001) after the intervention. The relative values of ΔTTP and ΔABI showed a weak correlation (r = −0.330). Conclusions The quantitative measurement results based on PBV and CCQ-DSA techniques showed that the overall blood volume increased significantly and that the foot distal hemodynamics were significantly improved after endovascular treatment. DR in the ischemic area could r improve foot perfusion.